Re-valuing the amygdala - Morrison, Sara E. (2010)
Recent advances indicate that the amygdala represents valence: a general appetitive/aversive affective characteristic that bears similarity to the neuroeconomic concept of value. Neurophysiological studies show that individual amygdala neurons respond differentially to a range of stimuli with positive or negative affective significance. Meanwhile, increasingly specific lesion/inactivation studies reveal that the amygdala is necessary for processes – e.g., fear extinction and reinforcer devaluation – that involve updating representations of value. Furthermore, recent neuroimaging studies suggest that the human amygdala mediates performance on many reward-based decision-making tasks. The encoding of affective significance by the amygdala might be best described as a representation of state value – a representation that is useful for coordinating physiological, behavioral, and cognitive responses in an affective/emotional context.